A clinical audit of thrombolytic therapy in patients with normotensive pulmonary embolism and intermediate risk. (June 2014) - Nobre, Carla; Mesquita, Dinis; Thomas, Boban; Ponte, Teresinha; Santos, Luis; Tavares, João
Abstract Introduction: There is considerable debate regarding the use of thrombolytic therapy in patients with pulmonary embolism, normal blood pressure and intermediate clinical risk, as defined by right ventricular dysfunction on transthoracic echocardiography or elevated serum markers of cardiac necrosis. Aims and objectives: A clinical audit of normotensive patients diagnosed with acute pulmonary embolism using multi- detector computerized tomography pulmonary angiography (MDCTPA) and intermediate risk, was conducted to determine clinical outcomes at 30 days. The specific role played by imaging findings and clinical severity, on the decision to thrombolyse, was assessed. Methods: The two cohorts who did (n = 15) and did not receive thrombolysis (n = 20) were compared for age, heart rate, blood pressure and oxyhemoglobin saturation at presentation, and the simplified PESI score was calculated in each patient. MDCTPA findings suggestive of adverse clinical outcome including central PE and an increased RV/LV diameter were determined for each patient. RV dysfunction on echocardiography was compared to clinical scoring, and findings on MDCTPA. Results: The patients who received thrombolytic therapy were younger (48.6 ± 19.11 years versus 64.2 ± 13.83 years) (P < 0.01) and had a higher heart rate (107.6 ± 17.1/min versus 91.7 ± 17.8/min) (P < 0.05). More patients with a higher clinical severity, as determined by the simplified PESI score (12/20) and a higher shock index (0.94 ± 0.23), were thrombolysed as compared to the proportion with a lower score (3/15) (P < 0.05) or index (0.70 ± 0.20) (P < 0.005). In-hospital mortality and hemorrhagic complications at 30 days were zero in both groups. RV dysfunction by echocardiography was not a strong determinant for choosing thrombolytic therapy while central PE on MDCTPA tilted the decision towards thrombolysis. Conclusion: Our clinical audit revealed a predilection to use thrombolysis in younger patients with clinical severity and imaging findings on MDCTPA being the key drivers. A perception of a fragile hemodynamic status, as implied by a higher heart rate and shock index, despite a normal BP probably inclined us to thrombolyse.